Characterization of Activated Carbon from Palm Oil Solid Waste Using HCl Activation and Carbonization Technique - Sani Sani; Nurul Widji Triana; Ika Nawang Puspitawati; Nur Mila Eka Zaliyanty; Mochammad Arip Pancar Agung (Program Studi Teknik Kimia, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
The increasing volume of palm oil solid waste in Indonesia offers an opportunity for valorization into high-value materials. This study explores the potential of converting palm oil waste—comprising empty fruit bunches, shells, and fibers—into activated carbon through hydrochloric acid activation. The carbonization process was varied across five temperature levels (250–450 °C) and durations (60–120 minutes) to determine optimal conditions that meet the criteria of SNI 06-3730-2021. Post-carbonization, chemical activation was conducted using a 20% HCl solution. The most favorable result was obtained at 450 °C for 105 minutes, yielding activated carbon with 81.68% fixed carbon, 3.85% moisture, 10.29% volatile matter, and 4.18% ash content. Furthermore, adsorption capacities reached 763.98 mg/g for iodine and 178.82 mg/g for methylene blue. These findings suggest that palm oil waste can be effectively transformed into activated carbon that satisfies national quality standards.